UJI TOKSISITAS DETERJEN CAIR TERHADAP IKAN MAS (Cyprinus carpio L.) Liquid Detergent Toxycity Test Againts of Cyprinus carpio L. - Siti Devi Permata Sari Lubis; Budi Utomo; Riri Ezraneti (AQUACOASTMARINE, 2014)
Liquid detergent is one of the waste that goes into the aquatic continuously. Liquid detergent containing alkyl benzene sulphonate which are difficult to decompose in the waters and can beharmful to aquatic oraganism. This study aims to determine the toxic effects caused by liquid detergen, with preliminary, and definitive test in: 0 ppm, 17.78 ppm, 31.62 ppm, 56.23 ppm, 100 ppm concentrations of liquid detergent. 700 of fish seeds Cyprinus carpio L. was used, with size of 5 - 6. Data were analyzed by the method of Hubbert. These results indicated that the liquid detergent had the fish toxicant and high detergent concentrations increased the toxicity. The concentration of liquid detergent for LC 50 96 was 44,66 ppm. This solution of liquid detergent at 44,66 ppm killed test by 50% in 96 hours. High detergent concentration in biota reduced the dysolved oxygen and increased temperature, which both environmental factors might cause the death of fish in the waters.Keywords: Cyprinus carpio L, liquid detergent, toxicity.